PERAN LEMBAGA KEUANGAN MIKRO SYARIAH DALAM MEMBANGUN EKONOMI YANG BERKELANJUTAN DAN INKLUSIF - Sari, Widya Ratna; Sulistyowati (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to look at the role of Islamic Microfinance Institutions in Building a Sustainable and Inclusive Economy. This study uses a library research approach because the data sources come from various literature such as articles, books, and journals from previous studies regarding the role of Islamic Microfinance Institutions in Building a Sustainable and Inclusive Economy. The results of the discussion show: from OJK data (2021) it can be seen that the development of LKMS both in terms of assets, the amount of financing distributed, as well as the public savings that have been collected shows an increasing trend. This means that the existence of LKMS has a significant influence on the pace of sustainable economic development, of course, the realization of inclusive finance. Thus, the role of Islamic microfinance institutions in building a sustainable and inclusive economy in Indonesia proves to be important and relevant. Through an inclusive approach, based on Sharia principles and social and environmental responsibility, Sharia microfinance institutions can become key drivers in achieving sustainable and inclusive economic development goals in Indonesia.